The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1097/hjh.0000000000000384
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-office blood pressure and target organ damage in children and adolescents

Abstract: The available evidence suggests a moderate but significant association between ambulatory BP and preclinical organ damage, mainly based on studies in nephropathy and/or diabetes. More data are needed in essential hypertension without nephropathy or diabetes, as well as with home measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(65 citation statements)
references
References 110 publications
1
62
0
2
Order By: Relevance
“…Home BP is lower than daytime ambulatory BP in children and adolescents (65,(68)(69)(70). Some preliminary evidence exists that home BP in children correlates with target organ damage (TOD) better than office BP (71), and that it may also better reflect the effect of risk factors on BP, such as family history or obesity (66,(72)(73). Two research groups reported good performance of home BP to 16 diagnose white-coat HTN, but a low sensitivity and positive predictive value to predict masked HTN compared to ABPM (68,74).…”
Section: Home Blood Pressurementioning
confidence: 99%
“…Home BP is lower than daytime ambulatory BP in children and adolescents (65,(68)(69)(70). Some preliminary evidence exists that home BP in children correlates with target organ damage (TOD) better than office BP (71), and that it may also better reflect the effect of risk factors on BP, such as family history or obesity (66,(72)(73). Two research groups reported good performance of home BP to 16 diagnose white-coat HTN, but a low sensitivity and positive predictive value to predict masked HTN compared to ABPM (68,74).…”
Section: Home Blood Pressurementioning
confidence: 99%
“…1,6 Home BP Monitoring Surveys in the United States, Canada, and Germany showed that >70% of the pediatric nephrologists use home BP monitoring in children with hypertension or renal disease, and 64% of them consider these measurements as more important than the office measurements. 11,12 Home BP monitoring in children has been less well studied than ambulatory monitoring 1,13,14 and shown to be useful in the detection of white-coat and masked hypertension. 15 As ambulatory BP monitoring cannot be easily performed frequently, home BP monitoring is recommended for regular follow-up of treated hypertension in children, aiming to improve the assessment of BP control.…”
Section: Auscultatory Bp Measurement In Childrenmentioning
confidence: 99%
“…A considerable percentage of children with elevated blood pressure show increased left ventricular hypertrophy. 12 The consortium of cardiovascular children cohorts observed that persistent elevated blood pressure was associated with higher increase of the carotid intima media thickness in adults compared with children without high blood pressure or with children in whom high blood pressure normalized across the observation period. 13 Indirectly, this result also points to a potential for prevention.…”
Section: Hypertensionmentioning
confidence: 99%